2022
DOI: 10.1007/s00426-022-01695-7
|View full text |Cite
|
Sign up to set email alerts
|

Can false denials turn fact into fiction? The effect of false denials on memory for self-performed actions

Abstract: We examined the mnemonic effects of falsely denying a self-performed action. Specifically, participants (N = 30) performed, imagined, or received no instruction about 24 action statements (e.g., “cross your arms”). Next, their memory for whether they had performed, imagined, or did nothing (i.e., received no instructions) with these actions was tested. Subsequently, participants were instructed to repeatedly deny an action they had performed (false denial) and to repeatedly claim to have performed an action th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, research has shown that suggestion-based false memories and spontaneous false memories are not necessarily related to one another, and studying false memories in different paradigms can lead to different results (Otgaar & Candel, 2011;Otgaar et al, 2017;Ost et al, 2013). Moreover, the current paper employed a victim perspective, whereas Otgaar et al (2020) studied false denials and false memories from a witnessing perspective, which might impact memory effects differently (Bücken et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, research has shown that suggestion-based false memories and spontaneous false memories are not necessarily related to one another, and studying false memories in different paradigms can lead to different results (Otgaar & Candel, 2011;Otgaar et al, 2017;Ost et al, 2013). Moreover, the current paper employed a victim perspective, whereas Otgaar et al (2020) studied false denials and false memories from a witnessing perspective, which might impact memory effects differently (Bücken et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the current paper employed a victim perspective, whereas Otgaar et al. (2020) studied false denials and false memories from a witnessing perspective, which might impact memory effects differently (Bücken et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations